Observer and Nonlinear Control Design of VSC-HVDC Transmission System. (February 2023) - El Myasse, I.; El Magri, A.; Kissaoui, M.; Lajouad, R.; Giri, F.; Watil, A.; Bahatti, L.
Abstract: This paper deals with the problem of controlling power systems that contain Voltage Source converters based on High Voltage Direct Current (VSC-HVDC). Specifically, the system under study consists of two power grids and two VSC stations connected via a long HVDC cable. Using the backstepping design technique, we design a nonlinear controller that meets three control objectives: (i) tight output voltage regulation of the HVDC cable; (ii) guarantee the power factor correction (PFC) at both sides of the HVDC system; (iii) regulation of the active power at the inverter station. Furthermore, we design a high-gain observer that provides the controller with online estimates of all states based on the measurements of the HVDC input voltage and current in the cable. Finally, one provides a stability analysis of the output feedback controller and simulation results highlighting its performances. Highlights: A nonlinear control strategy for a VSC HVDC transmission system is proposed. A nonlinear observer is employed for the online estimation of the HVDC cable state. Output feedback is performed based on the online estimation provided by the nonlinear observer. The robustness of the output feedback controller is validated by simulation.